INOVASI DIGITAL DAN PEMAHAMAN INNOVATIVE CREDIT SCORING DALAM MENINGKATKAN DAYA SAING UMKM DENGAN DUKUNGAN FINTECH PAYMENT: STUDI LITERATUR REVIEW - Muhammad Distian Andi Hermawan (Universitas Dian Nuswantoro, 2025)
This study seeks to provide a thorough overview of the literature on how digital innovation, such fintech payments and an understanding of ICS, may be essential to enhancing the competitiveness of MSMEs. The literature review technique is used in this study's qualitative methodology. The primary goal of this study is to examine, assess, and combine the outcomes of numerous prior studies, which is why this approach was selected. The qualitative review analysis method, which involves carefully evaluating the content, results, and contributions of each piece, was used to perform the data analysis. The study findings reveal that digital innovation improves efficiency and market penetration, fintech payments speed up transactions and establish a financial digital footprint, and ICS makes use of technology to provide financial services. this alternative data to evaluate creditworthiness more equitably and precisely. These three elements' synergy fosters trust between financial institutions and MSMEs while also promoting simple access to funding and operational efficiency. With the support of data- and innovation-based financial technology applications, it is a crucial strategy for empowering Indonesian SMEs